CB1 Cannabinoid Receptors Stimulate Gβγ-GRK2-Mediated FAK Phosphorylation at Tyrosine 925 to Regulate ERK Activation Involving Neuronal Focal Adhesions - Dalton, George D.; Carney, Skyla T.; Marshburn, Jamie D.; Norford, Derek C.; Howlett, Allyn C. (Frontiers in Cellular Neuroscience, 2020)
CB1 cannabinoid receptors (CB1) are abundantly expressed in the nervous system where they regulate focal adhesion kinase (FAK) and the mitogen-activated protein kinases (MAPK) extracellular signal-regulated kinase 1 and 2 (ERK1/2). However, the role of CB1-stimulated FAK 925 tyrosine phosphorylation (Tyr-P) in regulating ERK1/2 activation remains undefined. Here, immunoblotting analyses using antibodies against FAK phospho-Tyr 925 and ERK2 phospho-Tyr 204 demonstrated CB1-stimulated FAK 925 Tyr-P and ERK2 204 Tyr-P (0-5 min) which was followed by a decline in Tyr-P (5-20 min). CB1 stimulated FAK-Grb2 association and Ras-mediated ERK2 activation. The FAK inhibitors Y11 and PF 573228 abolished FAK 925 Tyr-P and partially inhibited ERK2 204 Tyr-P. FAK 925 Tyr-P and ERK2 204 Tyr-P were adhesion-dependent, required an intact actin cytoskeleton, and were mediated by integrins, Flk-1 vascular endothelial growth factor receptors, and epidermal growth factor receptors. FAK 925 Tyr-P and ERK2 204 Tyr-P were blocked by the Gβγ inhibitor gallein, a GRK2 inhibitor, and GRK2 siRNA silencing, suggesting Gβγ and GRK2 participate in FAK-mediated ERK2 activation. Together, these studies indicate FAK 925 Tyr-P occurs concurrently with CB1-stimulated ERK2 activation and requires the actin cytoskeleton and Gi/oβγ-GRK2-mediated cross-talk between CB1, integrins, and receptor tyrosine kinases (RTKs).